Citrus australasica F. Muell. Leaf Extracts are Ineffective Inhibitors of the Growth of a Panel of Bacterial Pathogens - Mpala, Lindy; Chikowe, Getmore; Cock, Ian E (Asian Journal of Biological and Life Sciences)
Introduction: Closely related plant species often share similar secondary metabolites and bioactivities and are therefore good targets for bioactivity testing when one or more species within a genus are known to possess therapeutic properties. The genus Citrus has a long history of ethnobotanbical usage in many areas of the world. Many species are known to have therapeutic properties, several species of which have well established antibacterial bioactivities. Materials and Methods : The ability of Citrus australasica F. Muell. leaf extracts to inhibit the growth of a panel of bacterial pathogens was investigated by disc diffusion assay. Toxicity was examined using the Artemia franciscana nauplii bioassay. Results: The C. australasica methanolic and aqueous extracts were ineffective at inhibiting the growth of gram-positive and gram-negative panels of bacteria and were nontoxic in the Artemia lethality assay following 24 hr exposure. Conclusion: Despite its close taxonomic relationship with several bioactive Citrus spp. with antibacterial activity, C. australasica leaf extracts were ineffective bacterial growth inhibitors. However, these extracts may have other therapeutic properties and testing against protozoa, fungi, virus and tumour cells is required.
Keywords: Rutaceae; Finger lime; Caviar lime; Pharmacognosy; Traditional medicine; Medicinal plants; Toxicity.